Penyuluhuan Budi Daya Ternak Sapi Strategi Alternatif Peningkatan Indeks Pembangunan Manusia di Desa Pawenang Kecamatan Jati Nunggal Kabupaten Sumedang - Endang Komara; Hanafiah (Bandung Conference Series: Economics Studies, 2024)
Abstract. The problem of increasing the Human Development Index in Pawenang Village, Jatinunggal District, Sumedang Regency is still faced with various obstacles including the disparity in accessibility of education, disparity in healthy living, and disparity in income per capita for a decent life that is not yet evenly distributed. One of the alternative strategies to boost these problems is the need for counseling which aims to refresh as well as to share problems, knowledge, experiences, and solutions related to cattle cultivation, both related to feed management (Feeding), breeding / breeding (Breeding) and Maintenance Management. The method used was Seminar-shaped counseling delivered to 50 (fifty) farmers at the Pawenang Village Hall whose participants were mostly sheep, goat and cattle farmers. This activity is expected to be an inspiration and solution towards increasing per capita income, increasing Expected Years of Schooling (HLS) and Average Years of Schooling (RLS), as well as increasing life expectancy and healthy living in Pawenang Village, Jatinunggal District, Sumedang Regency. Abstrak. Permasalaham peningkatan Indeks Pembangunan Manusia di Desa Pawenang Kecamatan Jatinunggal Kabipaten Sumedang masih dihadapkan kepada berbagai kendala diantaranya masih adanya dispariritas aksesibilitas pendidikan, disparitas hidup sehat, dan disparitas pendapatan perkapita untuk hidup layak yang belum merata. Salah satu trategi alternative untuk mendongkrak masalah tersebut perlu adanya penyuluhan yang bertujuan dalam rangka penyegaran kembali sekaligus untuk berbagi masalah, pengetahuan, pengalaman, dan solusia berkaitan Budi Daya Ternak sapi, baik berkaitan dengan pengelolaan pakan (Feeding), pengembang biakan/pembibitan (Breeding) maupun Manajemen Pemeliharaan. Metode yang digunakan berupa Penyuluhan berbentuk Seminar yang disampaikan kepada 50 (lima puluh) peternak di Balai Desa Pawenang yang pesertanya mayoritas sebagai peternak domba, kambing dan peternak sapi. Dengan adanya kegiatan ini diharapkan dapat menjadi inspirasi dan solusi menuju peningkatan pendapatan perkapita, peningkatan Harapan Lama Sekolah (HLS) dan Rata-rata Lama Sekolah (RLS), serta peningkatan harapan hidup dan hidup sehat di Desa Pawenang Kecamatan Jatinunggal Kabupaten Sumedang.